Functional CCR9 expression is associated with small intestinal metastasis - Letsch, Anne; Schadendorf, Dirk (The journal of investigative dermatology, 2015)
In general, metastases to the small intestine are rare, and mostly occur in melanoma. CCR9 has been shown to be the principal chemokine receptor for the thymus expressed chemokine (TECK), a chemokine selectively expressed in the small intestine and thymus. Here we show that CCR9 is highly expressed on melanoma cells and all melanoma cell lines isolated from small intestinal metastases, and on a proportion of cell lines from other sites. Only melanoma cells and cell lines from small intestinal metastases, however, were responsive to the CCR9 ligand TECK, as assessed by receptor downregulation and by actin polymerization. CCR9 expression was also found on the adenocarcinoma cell line CaCo-2 expressing characteristics of enterocytic differentiation, but not on any other cell line isolated from colorectal, breast, and lung cancer. Our data provide evidence that the aberrant functional cell surface expression of an organ-specific chemokine receptor is associated with metastasis to this site. The regulation of receptor function seems to be a critical step in the metastatic process.
Elektronische Reproduktion der Druckausgabe
Gesehen am 25.11.2020